Information systems and management in media and entertainment industries - Lugmayr, Artur; Stanoevska, Katarina; Stojmenova, Emilija; Wellington, Robert (International series on computer entertainment and media technology, 2016)
This book defines an agenda for research in information management and systems for media and entertainment industries. It highlights their particular needs in production, distribution, and consumption. Chapters are written by practitioners and researchers from around the world, who examine business information management and systems in the larger context of media and entertainment industries. Human, management, technological, and content creation aspects are covered in order to provide a unique viewpoint. With great interdisciplinary scope, the book provides a roadmap of research challenges and a structured approach for future development across areas such as social media, eCommerce, and eBusiness. Chapters address the tremendous challenges in organization, leadership, customer behavior, and technology that face the entertainment and media industries every day, including the transformation of the analog media world into its digital counterpart. Professionals or researchers involved with IT systems management, information policies, technology development or content creation will find this book an essential resource. It is also a valuable tool for academics or advanced-level students studying digital media or information systems.